From biomass to value: a decision support analysis for market-driven microalgal biorefineries - Makkonen, Sara (My University, 2025)
In this thesis a decision support analysis is done for Aircohol Oy to aid strategic decision-making. Aircohol Oy cultivates microalgae for sustainable circular economy applications. The aim of the decision support analysis is to evaluate the most profitable biorefinery strategies in the current market situation. Microalgae are versatile raw material that contains valuable compounds for various industries. The ratio of the compounds within a microalgae cell can be manipulated by adjusting cultivation parameters. This is an important feature that makes microalgae production flexible as the cell composition dictates the product portfolio. In this thesis, the compositions of five microalgae cultivations are compared to identify the one with the highest profit potential. While the intrinsic value of the microalgal compounds is dictated by the biochemical properties, their market value is ultimately dictated by demand, which varies between the products. The market values are investigated with a market analysis and interviewing potential customers. Moreover, these products not only differ in value but also in refining cost. Biorefining is a concept with which all valuable microalgal products are isolated to maximise overall value. However, the choice of a biorefinery strategy must be carefully justified by a decision support analysis. The most profit is created when the selected biorefinery strategy is aligned with the desired product fractions, as dictated by both the biomass composition and market demand. In this thesis different biorefinery strategies are evaluated through techno-economic assessment (TEA). Only the process related costs are within the scope of this assessment, and other costs such as plant establishment, maintenance and labour costs are excluded, although they are commonly included. Based on this evaluation, ten biorefinery strategies are designed. The techno-economic parameters identified in the decision support analysis are compiled in a flexible decision support system. The most profitable biorefinery strategies in current market situation were the production of broken and dried microalgae cells and isolating protein, mono- and polysaccharides from the insoluble fraction with two-step filtration. This decision support analysis must be updated as prevailing market situation and regulations change. Also, the secondary data used in this TEA should be updated and replaced with primary data as it becomes available. Decision support analysis is crucial to become and remain competitive in changing market situation where market values and costs fluctuate and new regulations emerge. Finally, the development of microalgae strains and biorefinery technologies enable new applications and generate novel process parameters.
Keywords: Microalgae, biorefinery, circular economy, sustainable business, strategic decision-making